2022
DOI: 10.1021/acsomega.2c00579
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Inflammatory Response and Promotion of Osteogenic Activity of Zinc-Doped Micro-Arc Titanium Oxide Coatings

Abstract: An early and sustained immune response can lead to chronic inflammation after the implant is placed in the body. The implantable materials with immunomodulatory effects can reduce the body’s immune response and promote the formation of ideal osseointegration between the implants and bone tissue. In this study, zinc-coated titanium micro-arc oxide coating was prepared on titanium surface by micro-arc oxidation. The physical properties, anti-inflammation, and osteogenesis of the material were evaluated. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 58 publications
(108 reference statements)
1
13
0
1
Order By: Relevance
“…The titania layer was prepared by microarc oxidation (MAO), , which is a promising process for the deposition of bioceramic oxide coatings on valve metals. This technique has allowed us to prepare the barrier porous TiO 2 (anatase) coating, which can potentially reduce inflammation around tissues . Moreover, the prepared surface promotes HAp deposition because of the presence of Ti–OH groups stimulating HAp nucleation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The titania layer was prepared by microarc oxidation (MAO), , which is a promising process for the deposition of bioceramic oxide coatings on valve metals. This technique has allowed us to prepare the barrier porous TiO 2 (anatase) coating, which can potentially reduce inflammation around tissues . Moreover, the prepared surface promotes HAp deposition because of the presence of Ti–OH groups stimulating HAp nucleation .…”
Section: Introductionmentioning
confidence: 99%
“…This technique has allowed us to prepare the barrier porous TiO 2 (anatase) coating, which can potentially reduce inflammation around tissues. 30 Moreover, the prepared surface promotes HAp deposition because of the presence of Ti–OH groups stimulating HAp nucleation. 19 Ca–P coatings were obtained by a high-performance procedure of electrophoretic deposition (ED), which also allowed the preparation of a thick and porous Ca–P layer with minimal changes in its chemical and phase composition.…”
Section: Introductionmentioning
confidence: 99%
“…Zn and its alloys have received increasing interest as new alternative biodegradable metals due to their biological merits and ideal degradation rate. ,, Zn possesses standard electrochemical potential between those of magnesium and iron, suggesting an appropriate physiological degradation rate. , Zn 2+ is considered an essential element in the human body and to take part in many important biological reactions, including cell growth, enzymatic reaction, wound healing, and immune reaction. ,, Some in vivo experiments on animals revealed that Zn exhibited a strong antiatherogenic character and good hemocompatibility …”
Section: Introductionmentioning
confidence: 99%
“…Zn and its alloys have received increasing interest as new alternative biodegradable metals due to their biological merits 1 8 and ideal degradation rate. 5 , 7 , 9 12 Zn possesses standard electrochemical potential between those of magnesium and iron, suggesting an appropriate physiological degradation rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation